1997
DOI: 10.1111/j.1745-4549.1997.tb00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Disinfestation of Cowpea Seeds Contaminated by Callosobruchus Maculatus

Abstract: Development of Callosubruchus maculatus (F.) in cowpea seeds (Vigna unguiculata (L.) Walp) can be prevented by sterilization of the adult forms and destruction of the eggs, larvae and pupae using an ionizing treatment at doses less than 100 Gy, without causing unfavorable nutritional consequences. Storage of these cowpea seeds in polyethylene bags of a thickness greater than 100 μm avoids all recontamination by this weevil. Economically, the irradiation of such a foodstuff would certainly be worthwhile in Sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…1999; Wu et al . 2002; Al‐bashir 2004) such as cowpea and maize resulting in desirable outcomes such as insect and pest infestation prevention (Diop et al . 1997) and increased cowpea flour protein digestibility (Dario and Salgado 1994).…”
Section: Introductionmentioning
confidence: 99%
“…1999; Wu et al . 2002; Al‐bashir 2004) such as cowpea and maize resulting in desirable outcomes such as insect and pest infestation prevention (Diop et al . 1997) and increased cowpea flour protein digestibility (Dario and Salgado 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Boshra (1994) reported that the dose required to disinfest and/or sterilize both males and females was 120 Gy. Ionizing treatment dose less than 100 Gy had utilized to sterilize the adults and elimination of the eggs, larvae, and pupae without bringing about troublesome healthful outcomes (Diop, Marchioni, Ba, & Hasselmann, 1997). IAEA (2002) had prescribed that the 100 Gy is the minimum dose required to sterilize the adult of C. chinensis.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Irradiation and essential oil utilization are two methods that could be used in IPM (Sharma and Seth, 2005). Both genera Bruchus and Callosobruchus, the main stored-product pests, are observed to be sensitive to irradiation (Diop et al, 1997). Roy and Prasad (1993) noticed that a dose of 1 kGy of gamma radiation killed all the adults of Callosobruchus chinensis L. within a week.…”
Section: Introduction 12mentioning
confidence: 99%